Biotechnology in direct air capture, enhanced weathering, and methane removal: emerging opportunities and gaps - Reginato, Paul L. (Frontiers in Climate, 2025)
Net emissions targets for the coming decades demand that new greenhouse gas removal (GHGR) technologies be developed and scaled to up to 10 GtCO2e/yr. by 2050. Due to the interdisciplinarity and novelty of GHGR technologies, GHGR research faces challenges of adapting technical disciplines to new domains and broadly empowering researchers with the knowledge necessary to identify and solve key problems. This Perspective discusses the significant, but underexplored, role biotechnology could play in several GHGR technologies as well as the common research, community, and knowledge gaps that are limiting progress. The GHGR technologies of focus are (1) the potential for the enzyme carbonic anhydrase to catalyze CO2 exchange in direct air capture; (2) the potential utility of microbes for accelerating soil-based or reactor-based enhanced rock weathering; and (3) the potential for methanotrophic bacteria or methane monooxygenase enzymes to oxidize methane for atmospheric methane removal via enhanced methanotrophy or bioreactors. Research progress on those GHGR methods is strongly limited by lack of interdisciplinary research community development as well as knowledge gaps. There is a need for clear and accessible articulation of actionable problems, ideally paired with risk-tolerant funding opportunities, as a tool for recruiting and empowering relevant researchers to these under-addressed technology areas.